Digital Humanities and the Common Good - Fletcher, Pamela; Hall, Crystal (Maine Policy Review, 2015)
Digital humanities is an emerging field of scholarship, teaching, and outreach, in which digital and computational methods are brought to bear on the traditional materials and questions of the humanities. Some claim this new field will save the humanities; others worry that it will crowd out traditional methods of reading, looking, writing, and teaching. It is our belief that neither of these outcomes is likely. Instead, the authors believe that bringing computational tools to the study of the humanities and humanistic inquiry’s focus on questions of historical perspective and context, ethics, and value to the study of technology will benefit both areas. In this article, we focus specifically on how the humanities in the digital age can be useful for the informed decision making central to crafting effective public policy and how public policies can support this new era of the humanities.
Keywords: digital humanities; big data; Internet neutrality; libraries; museums